Technology standards and recommendations for operationalizing agricultural data protection - CGIAR Platform for Big Data in Agriculture (2020)
Guidance linking data protection policies (e.g. GDPR) and ethical frameworks to relevant formal technology standards (e.g. NIST, ISO) for implementing data protection infrastructure, and a framework for assessing risk .